Construction of a high-resolution genetic linkage map and comparative genome analysis for the reef-building coral Acropora millepora - Wang, Shi (BioMed Central, 2009)
A high-resolution genetic linkage map for the coral Acropora millepora is constructed and compared with other metazoan genomes, revealing syntenic blocks.